Veterinary absorbable orthopedic implant material and preparation method thereof
By mixing bioabsorbable polymers with inorganic substances and using injection molding and heat treatment processes, veterinary resorbable orthopedic implant materials with excellent mechanical properties and good biocompatibility are solved, and the cost in the prior art is solved. High, material problems and biocompatibility issues have improved the effectiveness of animal fracture treatment and animal welfare.
Patent Information
- Application Number
- CN202411637096.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-18
AI Technical Summary
Existing veterinary orthopedic implants have high costs, material problems, biocompatibility and immune response, and difficulty in tracking long-term effects, which affects the treatment effect of fractures and animal welfare in animals.
Veterinary resorbable orthopedic implant materials prepared by mixing bioabsorbable polymers with inorganic weight ratios of 60-95:5-40, improve the mechanical properties and biocompatibility of the materials through injection molding and heat treatment processes. .
It has achieved the reduction of production costs, improved the mechanical properties and biocompatibility of materials, reduced the risk of immune response in animals, and simplified the tracking of long-term effects, improving the effectiveness of animal fracture treatment and animal welfare.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of veterinary medical devices, and in particular to an absorbable veterinary orthopedic implant material and a preparation method thereof. Background Art
[0002] At present, veterinary orthopedic implant materials are used in a variety of animal trauma fracture repair scenarios. The main application areas and application methods are: Veterinary absorbable bone plates: the main orthopedic implants for pet internal fixation, which can avoid stress shielding of metal bone plates on the bones under the plates, bone loss, and local inflammation and metal ion toxicity caused by long-term implantation of metal bone plates, enhance the biocompatibility of internal fixation bone plates, and utilize the characteristics of plastic materials to facilitate doctors' operation and use; Veterinary absorbable screws: locking screws that can be used with bone plates, or fixing screws that can be used alone. These screws have strong enough locking strength and bending strength to allow bones to heal healthily, and they can slowly degrade after long-term implantation, and the screw holes disappear, avoiding long-term implantation problems caused by metal screws; Veterinary absorbable Kirschner wires: As orthopedic auxiliary implants, they are mainly used for surgical assistance and internal fixation of bone fractures, joints, ligaments, femoral heads, etc.; they have sufficient rigidity and bending strength, and because of the characteristics of the material, they have better plasticity than metal Kirschner wires when bending and cutting, and they can still degrade in the bone, avoiding intramedullary problems caused by long-term implantation of metal Kirschner wires.
[0003] Therefore, veterinary absorbable orthopedic implants have the ability to replace current veterinary clinical orthopedic implants, and for animals, they can enhance animal biocompatibility and improve animal welfare.
[0004] The preparation methods of veterinary orthopedic implants on the market include a variety of technologies and processes, involving machining, CNC machining, 3D printing and other technologies to obtain orthopedic implants. The following are some key preparation technology descriptions: (1) Machining: By using various mechanical processing methods such as milling, turning, drilling, etc. to accurately manufacture pressurized metal plates, bone screws, and Kirschner wires. (2) CNC technology: Using computer numerical control technology for precise processing, it is possible to manufacture metal materials with complex shapes and fine processing, thereby realizing the manufacture of more special-shaped bone plates such as "point contact" and "pressurized bone plates", screws with finer threads, and Kirschner wires with more structures. (3) 3D printing technology: According to the three-dimensional model of the design drawing, the product is manufactured layer by layer to achieve customized design and complex structure construction. At present, 3D technology can involve the printing of some metal materials and most polymer materials. (4) Surface treatment technology: By polishing, sandblasting, coating and other methods on the surface of the bone plate, the surface properties of the bone plate, bone screws, and Kirschner wires are improved to improve their biocompatibility and corrosion resistance. (5) Heat treatment: Improve the microstructure of metal materials through heat treatment, increase their strength and toughness, and increase mechanical properties. (6) Injection molding: Make a mold according to the designed three-dimensional model, use the melting state and density, viscosity and other parameters of the plastic material, pressurize and inject it into the mold, and cool it to obtain a polymer orthopedic implant. (7) Compression molding: Add the material to the mold, use the melting temperature of the material and the pressure of the mold to press the material into the shape of the mold, and cool it to obtain a polymer orthopedic implant.
[0005] The combination of these technologies provides a variety of options for the development of veterinary orthopedic implants, providing more ways to improve treatment outcomes, animal welfare, reduce side effects, and reduce costs.
[0006] However, there are still some problems and defects in the technology related to veterinary orthopedic implants, mainly: (1) Excessive cost: Metal materials are difficult to process, with low production efficiency and expensive materials, resulting in relatively high production costs. In addition, due to their poor plasticity, various types of products need to be made according to fracture locations, increasing costs for hospitals and pet owners. After veterinary orthopedic implants are implanted, they will not be removed a second time because the cost of surgery is high and no pet owner is willing to bear it, let alone the hospital. (2) Material issues: There are currently a variety of orthopedic implants made of various materials on the market, and each material has its limitations. Metal materials have problems such as stress shielding, metal corrosion, and MRI magnetic field response. Polymer materials may have problems with long-term stability. (3) Biocompatibility and immune response: Orthopedic implants may trigger an immune response in animals, resulting in compatibility issues between the implant and the host tissue. (4) Long-term effects and follow-up: Long-term monitoring of the effects of implants and animal recovery requires continuous attention, but currently few people in the market are conducting continuous observations.
[0007] In summary, all veterinary orthopedic implants on the market have defects. In the past twenty years or more, metal orthopedic implants that have been continuously updated in pet clinics have relatively large risks due to their high prices, material defects, and little attention to their long-term implant effects. Emerging polymer materials require deeper research in terms of their cost and material properties. However, in order to meet higher animal welfare requirements, save costs for pet hospitals and pet owners, and enable more animals to receive treatment when they have fractures. Summary of the invention
[0008] In order to solve the above technical problems, the present application provides a veterinary absorbable orthopedic implant material and a preparation method thereof.
[0009] The present application provides a veterinary absorbable orthopedic implant material, which is prepared by mixing a bioabsorbable polymer and an inorganic substance in a weight ratio of 60-95:5-40;
[0010] The bioabsorbable polymer is selected from one or more of polylactic acid (PLA), poly-L-lactic acid (PLLA), polyglycolic acid (PLGA);
[0011] The polylactic acid is a copolymer of dextrorotatory polylactic acid and laxative polylactic acid PLLA in a weight ratio of 0.5-2:98-99.5, with a molecular weight of 10w-40w, a glass transition temperature of 55-60°C, and a melting temperature higher than 175°C;
[0012] The molecular weight of the L-polylactic acid material is 10w-100w, the glass transition temperature is 55-75°C, and the melting temperature is higher than 175°C;
[0013] The polyglycolic acid material has a molecular weight of 10w-100w, a glass transition temperature of 30-70°C, and a melting temperature above 175°C;
[0014] The inorganic substance is selected from one or more of hydroxyapatite and calcium phosphate; the inorganic substance is a powder material with a size of 0.01-40 μm and a purity of 80%-99%, or the inorganic substance is a needle-shaped or columnar material with a diameter of 0.01-20 μm and an aspect ratio of 1:5-20, and a purity of 80%-99%.
[0015] By utilizing the technical solution of the present application, an absorbable veterinary orthopedic implant with excellent mechanical properties is obtained; this material can be used for animal fracture recovery to meet the basic needs of pet fractures and has broad market prospects and technical advantages.
[0016] Preferably, the veterinary absorbable orthopedic implant material is prepared by mixing a bioabsorbable polymer and an inorganic substance in a weight ratio of 70-80:20-30.
[0017] Preferably, the veterinary absorbable orthopedic implant material is prepared by mixing a bioabsorbable polymer and an inorganic substance in a weight ratio of 76:27.
[0018] Preferably, the bioabsorbable polymer consists of polylactic acid and cyclodextrin in a weight ratio of 85-95:5-15.
[0019] Furthermore, the bioabsorbable polymer consists of polylactic acid and cyclodextrin in a weight ratio of 88-93:7-12.
[0020] Preferably, the cyclodextrin is selected from one or more of α-cyclodextrin, γ-cyclodextrin, β-cyclodextrin, hydroxypropyl-β-cyclodextrin, and hydroxyethyl-β-cyclodextrin.
[0021] Preferably, the inorganic substance is a powder material with a size of 0.5-10 μm and a purity of 80%-99%.
[0022] Preferably, the size of the inorganic substance is a needle-shaped or columnar material with a diameter of 0.5-5 μm, an aspect ratio of 1:10-15, and a purity of 80%-99%.
[0023] In a second aspect, the present application provides a method for preparing the above-mentioned veterinary absorbable orthopedic implant material, which specifically comprises the following steps in sequence:
[0024] Grinding the bioabsorbable polymer to 45-300 mesh, drying under vacuum environment, and setting aside;
[0025] Drying the inorganic substance in a vacuum environment for later use;
[0026] The bioabsorbable polymer and the inorganic substance are mixed, stirred evenly, poured into a twin-screw extruder, blended at a temperature of 160-220° C., extruded, drawn, cooled and shaped at a temperature of 15-30° C., and cut at room temperature to obtain a blended raw material;
[0027] Dry the blended raw materials in a vacuum environment or a nitrogen environment at a temperature of 80-100°C for 2-4 hours; control the mold temperature between 50-90°C, adjust the temperature of the injection molding machine channel and the screw at each injection stage between 160-250°C, and perform injection molding and sampling;
[0028] The sample is heat treated at a temperature of 80-100°C for 100-140 minutes to release the stress of the product after injection molding to obtain the final product.
[0029] The above technical solution can adjust the crystallinity and molecular chain of the material by adjusting the specific parameters of each process stage so that the prepared veterinary absorbable orthopedic implant has more excellent performance.
[0030] In summary, the technical solution of this application has the following effects:
[0031] In terms of cost: this application adopts injection molding, which reduces the number of equipment and increases production efficiency compared to machining, and obtains more products with similar raw material prices; and this application can soften and plasticize at a certain temperature, so if the bones have a certain bending and twisting desire, they can be shaped on the original plate so that they can be fixed according to the direction of the bones, so as to fit perfectly; it reduces the need for hospitals to stock multiple products, resulting in waste of funds, thereby reducing the expenses of animal owners; for the current more complex polymer material applications, the solution used in this application has lower material costs while meeting the same therapeutic effect.
[0032] Material issues: The materials used in this application are bioabsorbable materials, and all the problems encountered by metal materials can be solved; and because the material used is not prepared with a single polymer material, it adopts a combination of inorganic and polymer, and the inorganic material is used to enhance the bending properties of the polymer, and the inorganic material is a bone material, which has a promoting effect in the fracture recovery process; and the surface of the material is not a smooth plane, which is conducive to cell attachment, and helps degradation and tissue regeneration.
[0033] Biocompatibility and immune response: This application has good biocompatibility; the raw materials have no known biocompatibility risks, and the polymer is a bioabsorbable polymer, without the risk of plastic accumulation in the body, and the inorganic matter is bone meal powder, which helps fracture healing; after long-term implantation, the material can be degraded in the body, and there will be no biocompatibility problems even with long-term implantation; the raw materials of this application have no known immune response, and the initial contaminating bacteria and insoluble particles are strictly controlled during the production process to reduce the risk of acquiring an immune response during the production process.
[0034] Long-term effects and follow-up: Since the main healing period of fracture healing is 6 months and bone remodeling is 6-24 months, the materials used in this application are tested for fracture healing effects within 24 months. After 24 months, there is no need to monitor them because they are degradable and will gradually disappear from the body after 24 months.
[0035] Optimizing the process of known polymer and inorganic mixtures: In the production process of the present application, the bioabsorbable polymer particles are ground and crushed to obtain a bioabsorbable polymer plastic powder of 10-100 mesh, or the bioabsorbable polymer plastic powder of 10-100 mesh can be used directly. The inorganic material is selected as a powder of 0.01-40μm or a needle-shaped or columnar material with a diameter of 0.01-20μm and an aspect ratio of 1:5-20. The combination of the two can increase the uniformity of the inorganic material in the polymer; after injection molding, a heat treatment process is added, and the product is heat treated at a specific temperature and environment, thereby adjusting the product crystallinity and molecular chain, thereby increasing the bending strength of the product.
[0036] Through the above-mentioned technical methods, the present application not only solves the existing technical problems, but also improves the problems in the production process, improves the production efficiency, and enhances its ability to respond to the market. DETAILED DESCRIPTION
[0037] The present application is further described in detail below in conjunction with examples, comparative examples and performance testing experiments. These examples should not be construed as limiting the scope of protection claimed in the present application.
[0038] Example
[0039] Example 1
[0040] Example 1 provides an absorbable orthopedic implant material for animals and a preparation method thereof.
[0041] The preparation method of the veterinary absorbable orthopedic implant material in this embodiment is as follows:
[0042] Bioabsorbable polymer: It is composed of a mixture of polylactic acid in a weight ratio of 90:10 (polylactic acid is a copolymer of dextrorotatory polylactic acid and laxative polylactic acid PLLA in a weight ratio of 1g:99g, with a material molecular weight of 30w, a glass transition temperature of 58°C, and a melting temperature of 190°C) and hydroxypropyl-β-cyclodextrin.
[0043] Grind the bioabsorbable polymer into 50-100 mesh, dry it in a vacuum environment at 90°C, and set aside;
[0044] Drying the inorganic hydroxyapatite (needle-shaped material with a diameter of 0.5-5 μm, an aspect ratio of 1:10-15, and a purity of 85%) at 90° C. in a vacuum environment for later use;
[0045] 76 g of bioabsorbable polymer and 27 g of inorganic material were mixed, stirred evenly, poured into a twin-screw extruder, blended at 200° C., extruded, drawn, cooled and shaped at 20° C., and cut at room temperature to obtain a blended raw material;
[0046] The blended raw materials were dried under vacuum at 90°C for 3 hours; the mold temperature was controlled at 75°C, and the temperature of each injection stage of the injection molding machine channel and screw was adjusted to 200°C for injection molding and sampling;
[0047] The sample was heat treated in an oven at 90°C for 120 min to release the stress of the product after injection molding, thereby obtaining the final product.
[0048] Embodiment 2-5
[0049] Examples 2-5 respectively provide an absorbable veterinary orthopedic implant material and a preparation method thereof.
[0050] The difference between the above embodiment and embodiment 1 is that the amounts of the bioabsorbable polymer and the inorganic substance used are as follows.
[0051] In Example 2, the amount of the bioabsorbable polymer is 60 g, and the amount of the inorganic substance is 40 g.
[0052] In Example 3, the amount of the bioabsorbable polymer used is 95 g, and the amount of the inorganic substance used is 5 g.
[0053] In Example 4, the amount of the bioabsorbable polymer is 70 g, and the amount of the inorganic substance is 30 g.
[0054] In Example 5, the amount of the bioabsorbable polymer is 80 g, and the amount of the inorganic substance is 20 g.
[0055] The other parameters of the above embodiment are the same as those of embodiment 1.
[0056] Embodiment 6-15
[0057] Examples 6-15 respectively provide an absorbable veterinary orthopedic implant material and a preparation method thereof.
[0058] The difference between the above embodiment and embodiment 1 is that the types of bioabsorbable polymers are specifically as follows.
[0059] In Example 6: Bioabsorbable polymer: polylactic acid is used alone (polylactic acid is a copolymer of dextrorotatory polylactic acid and lavorotatory polylactic acid PLLA mixed in a weight ratio of 1g:99g, the material molecular weight is 30w, the glass transition temperature is 58°C, and the melting temperature is 190°C).
[0060] In Example 7: Bioabsorbable polymer: L-polylactic acid (molecular weight 50w, glass transition temperature 62°C, melting temperature 195°C) was used alone.
[0061] In Example 8: Bioabsorbable polymer: polyglycolic acid (molecular weight 50w, glass transition temperature 50°C, melting temperature 192°C) was used alone.
[0062] In Example 9: Bioabsorbable polymer: composed of a mixture of polylactic acid (PLA) in a weight ratio of 90:10 (PLA is a copolymer of dextrorotatory polylactic acid and lavorotatory polylactic acid PLLA in a weight ratio of 1g:99g, with a material molecular weight of 30w, a glass transition temperature of 58°C, and a melting point of 190°C) and β-cyclodextrin.
[0063] In Example 10: Bioabsorbable polymer: composed of a mixture of polylactic acid (PLA) in a weight ratio of 90:10 (PLA is a copolymer of dextrorotatory polylactic acid and lavorotatory polylactic acid PLLA in a weight ratio of 1g:99g, with a material molecular weight of 30w, a glass transition temperature of 58°C, and a melting point of 190°C) and α-cyclodextrin.
[0064] In Example 11: Bioabsorbable polymer: composed of a mixture of polylactic acid in a weight ratio of 80:20 (polylactic acid is a copolymer of dextrorotatory polylactic acid and laxative polylactic acid PLLA in a weight ratio of 1g:99g, with a material molecular weight of 30w, a glass transition temperature of 58°C, and a melting point of 190°C) and hydroxypropyl-β-cyclodextrin.
[0065] In Example 12: Bioabsorbable polymer: composed of a mixture of polylactic acid in a weight ratio of 85:15 (polylactic acid is a copolymer of dextrorotatory polylactic acid and laxative polylactic acid PLLA in a weight ratio of 1g:99g, with a material molecular weight of 30w, a glass transition temperature of 58°C, and a melting point of 190°C) and hydroxypropyl-β-cyclodextrin.
[0066] In Example 13: Bioabsorbable polymer: composed of a mixture of polylactic acid in a weight ratio of 95:5 (polylactic acid is a copolymer of dextrorotatory polylactic acid and laxative polylactic acid PLLA in a weight ratio of 1g:99g, with a material molecular weight of 30w, a glass transition temperature of 58°C, and a melting point of 190°C) and hydroxypropyl-β-cyclodextrin.
[0067] In Example 14: Bioabsorbable polymer: composed of a mixture of polylactic acid in a weight ratio of 88:12 (polylactic acid is a copolymer of dextrorotatory polylactic acid and laxative polylactic acid PLLA in a weight ratio of 1g:99g, with a material molecular weight of 30w, a glass transition temperature of 58°C, and a melting point of 190°C) and hydroxypropyl-β-cyclodextrin.
[0068] In Example 15: Bioabsorbable polymer: composed of a mixture of polylactic acid in a weight ratio of 93:7 (polylactic acid is a copolymer of dextrorotatory polylactic acid and laxative polylactic acid PLLA in a weight ratio of 1g:99g, with a material molecular weight of 30w, a glass transition temperature of 58°C, and a melting point of 190°C) and hydroxypropyl-β-cyclodextrin.
[0069] The other parameters of the above embodiment are the same as those of embodiment 1.
[0070] Examples 16-18
[0071] Examples 16-18 respectively provide an absorbable veterinary orthopedic implant material and a preparation method thereof.
[0072] The difference between the above embodiment and embodiment 1 is that the types of inorganic substances are specifically as follows.
[0073] In Example 16: the size of the hydroxyapatite inorganic material is a needle-shaped material with a diameter of 0.01-0.3 μm, an aspect ratio of 1:5-10, and a purity of 85%.
[0074] In Example 17: the size of the hydroxyapatite inorganic material is a needle-shaped material with a diameter of 10-20 μm and an aspect ratio of 1:15-20, and the purity is 85%.
[0075] In Example 18: the size of the hydroxyapatite inorganic material is 0.5-10 μm powder material.
[0076] The other parameters of the above embodiment are the same as those of embodiment 1.
[0077] Comparative Example
[0078] Comparative Examples 1-4
[0079] Comparative Examples 1-4 respectively provide an absorbable orthopedic implant material for animal use.
[0080] The differences between the above comparative example and Example 1 are specifically as follows.
[0081] In Comparative Example 1, the amount of the bioabsorbable polymer used was 55 g, and the amount of the inorganic substance used was 45 g.
[0082] In Comparative Example 2, the amount of the bioabsorbable polymer used was 99 g, and the amount of the inorganic substance used was 1 g.
[0083] In Comparative Example 3: the bioabsorbable polymer is composed of a mixture of polylactic acid (polylactic acid is a copolymer of PDLLA and L-lactic acid PLLA in a weight ratio of 10g:90g, with a material molecular weight of 25w, a glass transition temperature of 58°C, and a melting temperature of 190°C) in a weight ratio of 1:15 and hydroxypropyl-β-cyclodextrin.
[0084] In Comparative Example 4: the size of the hydroxyapatite inorganic material is a needle-shaped material with a diameter of 50-100 μm and an aspect ratio of 1:25-35, and a purity of 85%.
[0085] Performance testing
[0086] Determination of mechanical properties: The compressive strength and bending modulus of veterinary absorbable orthopedic implant materials were tested using the MTS-810 mechanical properties testing system of MTS Company, with a loading displacement rate of 0.5 mm / min. The bending strength of veterinary absorbable orthopedic implant materials was tested at room temperature, with a total of 3 groups of specimens.
[0087] Test results: as shown in Table 1.
[0088] Table 1 Performance test results of veterinary absorbable orthopedic implant materials prepared in Examples and Comparative Examples
[0089]
[0090]
[0091] Combined with the test results in Table 1, by using the technical solution of the present application, a veterinary absorbable orthopedic implant material with high compressive strength, high flexural strength and large elastic modulus is obtained; the above results show that the veterinary absorbable orthopedic implant material prepared by the present application has excellent mechanical properties.
[0092] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A veterinary absorbable orthopedic implant material, characterized in that: It is prepared by mixing a bioabsorbable polymer and an inorganic substance in a weight ratio of 60-95:5-40; The bioabsorbable polymer includes one or more of polylactic acid, poly(L-lactic acid), and poly(glycolic acid); The polylactic acid is a copolymer of right-handed polylactic acid and left-handed polylactic acid mixed in a weight ratio of 0.5-2:98-99.5, with a molecular weight of 10w-40w, a glass transition temperature of 55-60°C, and a melting temperature higher than 175°C; The molecular weight of the L-polylactic acid material is 10w-100w, the glass transition temperature is 55-75°C, and the melting temperature is higher than 175°C; The polyglycolic acid material has a molecular weight of 10w-100w, a glass transition temperature of 30-70°C, and a melting temperature above 175°C; The inorganic substance is selected from one or more of hydroxyapatite and calcium phosphate; the inorganic substance is a powder material with a size of 0.01-40 μm and a purity of 80%-99%, or the inorganic substance is a needle-shaped or columnar material with a diameter of 0.01-20 μm and an aspect ratio of 1:5-20, and a purity of 80%-99%.
2. The absorbable orthopedic implant material for animals according to claim 1, characterized in that: The invention is prepared by mixing a bioabsorbable polymer and an inorganic substance in a weight ratio of 70-80:20-30.
3. The absorbable orthopedic implant material for animals according to claim 2, characterized in that: It is prepared by mixing a bioabsorbable polymer and an inorganic substance in a weight ratio of 76:
27.
4. The absorbable orthopedic implant material for animals according to claim 1, characterized in that: The bioabsorbable polymer consists of polylactic acid and cyclodextrin in a weight ratio of 85-95:5-15.
5. The absorbable orthopedic implant material for animals according to claim 4, characterized in that: The bioabsorbable polymer consists of polylactic acid and cyclodextrin in a weight ratio of 88-93:7-12.
6. The absorbable orthopedic implant material for animals according to any one of claims 4, characterized in that: The cyclodextrin is selected from one or more of α-cyclodextrin, γ-cyclodextrin, β-cyclodextrin, hydroxypropyl-β-cyclodextrin, and hydroxyethyl-β-cyclodextrin.
7. The absorbable orthopedic implant material for animals according to claim 1, characterized in that: The inorganic substance is a powder material with a size of 0.5-10 μm and a purity of 80%-99%.
8. The absorbable orthopedic implant material for animals according to claim 1, characterized in that: The size of the inorganic substance is a needle-shaped or columnar material with a diameter of 0.5-5 μm and an aspect ratio of 1:10-15, and a purity of 80%-99%.
9. The method for preparing the absorbable orthopedic implant material for animals according to any one of claims 1 to 8, characterized in that: Specifically, the following steps are performed in sequence: Grinding the bioabsorbable polymer to 45-300 mesh, drying under vacuum environment, and setting aside; Drying the inorganic substance in a vacuum environment for later use; The bioabsorbable polymer and the inorganic substance are mixed, stirred evenly, poured into a twin-screw extruder, blended at a temperature of 160-220° C., extruded, drawn, cooled and shaped at a temperature of 15-30° C., and cut at room temperature to obtain a blended raw material; Dry the blended raw materials in a vacuum environment or a nitrogen environment at a temperature of 80-100°C for 2-4 hours; control the mold temperature between 50-90°C, adjust the temperature of the injection molding machine channel and the screw at each injection stage between 160-250°C, and perform injection molding and sampling; The sample is heat treated at a temperature of 80-100°C for 100-140 minutes to release the stress of the product after injection molding to obtain the final product.